Peruvian native medicine - Lastres, Juan B. (1943)
Good time is it, time to review, to review and analyze the Peruvian native medicine. The wave of unrest and anxiety waving the Orb; is no obstacle to calmly contemplate the past. History has always been a source of lessons; hence the usefulness of the aboriginal medicine penetrate and interrogate all remnants of ancient civilizations.